Ocimum sanctum Leaves Prevent Neuronal Cell Apoptosis Through Reduction of Caspase-3 and -9 Expressions and Inhibition of β-amyloid Oligomerization - Dinda Aliffia; Dinda Ayu Ramadhani; Widya Wasityastuti; Dewi Ratih Tirto Sari; Ulayatul Kustiati; Hevi Wihadmadyatami; Dwi Liliek Kusindarta (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Neurodegenerative diseases are characterized by the loss of neuronal function in the nervous system. In recent years, more than 45 million people worldwide have suffered from progressive loss of memory and cognitive functions caused by Alzheimer’s disease. Ocimum sanctum is one of the medicinal plants known to have neuroprotective abilities. This study was conducted to elucidate the anti-apoptotic effects of ethanolic extract of O. sanctum (EEOS) on PC12 and SH-SY5Y cells as well as interaction between main compounds of EEOS and β-amyloid (Aβ) peptide through in silico molecular docking.METHODS: The viability of TMT-induced PC12 and SH-SY5Y cells was assessed with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay and acridine orange/propidium iodide staining. Cell proliferation rate was measured with cell counting kit-8 (CCK-8) assay. Nuclear fragmentation was observed with Hoechst 33342 staining. Caspase -3 and -9 expressions were measured using enzyme-linked immunosorbent assay. Interactions between main compounds of EEOS and Aβ were visualized with in silico molecular docking.RESULTS: EEOS had the potential effect of maintaining cell viability, preventing the cell’s morphological changes, and inhibiting apoptosis via the caspase pathway in PC12 and SH-SY5Y cells. Meanwhile, flavonoid K, phenol, eugenol could interact with the active site of Aβ through hydrogen-bonding and hydrophobic interactions.CONCLUSION: EEOS could prevent neuronal cell apoptosis via downregulation of caspase-3 and -9. Main compounds of EEOS could interact with the active site of Aβ, and thereby might inhibit Aβ oligomerization. Thus, EEOS and its main compounds could be potential as neuroprotective agents for preventing neurodegenerative diseases.KEYWORDS: Ocimum sanctum, anti-apoptotic, β-amyloid, caspase, neurodegeneration